The Ways of Improving the Efficiency of the Import Substitution Strategy of Russian Federation - Shabalina, L.V.; Karaman, E.G. (Економічний вісник Донбасу, 2015)
The dynamics and structure of Russian Federation import in the current geopolitical situation were analyzed. The international experience and the types of import substitution policy were studied. Improvements and development of the innovative activity were proposed. The creation of national support center was grounded. У статті проаналізовано динаміку та структуру імпорта Російської Федерації, у геополітичній ситуації, що склалася, Вивчено зарубіжний досвід та типи здійснення політики імпортозаміщення. Запропоновано рекомендації щодо підвищення інноваційної діяльності. Обґрунтовано створення національного центру підтримки імпортозаміщення. В статье проанализирована динамика и структура импорта Российской Федерации в сложившейся геополитической ситуации. Изучен зарубежный опыт и типы осуществления политики импортозамещения. Предложены рекомендации по повышению инновационной деятельности. Обосновано создание национального центра поддержки импортозамещения.